Upaya Meningkatkan Kemampuan Berbicara Bahasa Arab Melalui Metode Eklektik Permainan Tebak Tepat Pasanganmu (TTP) pada Siswa Kelas XI IPA-2 MAN Kendal - Sunardi Sunardi (Nusantara: Jurnal Pendidikan Indonesia, 2021)
This study aims to improve Arabic language skills through the electric Guess Your Match (Tebak Tepat Pasanganmu) method for class XI IPA-2 students of MAN Kendal. In the even semester of the 2016/2017 academic year, there may be 32 students. This research is a classroom action carried out in two cycles; Each cycle consists of four stages: planning, observation, observation, evaluation, and reflection. The data instrument, data analysis, and data analysis techniques used tests and non-tests. The results showed that the average value at the first meeting of the first cycle was 70.84, and the second meeting was 74.59 so that the average value of the first cycle was 72.71. While the average value of the first meeting in cycle II was 80.03, and the second meeting was 86.86, then in cycle II the average value was 83.43. So that there was an increase from cycle I to cycle II of 14.75%. The results of non-test data analysis based on learning outcomes also showed a change in students' behaviour in class XI IPA-2 MAN Kendal. The researcher concluded that the pairing game guessing (Tebak Tepat Pasanganmu) method significantly improved the students' Arabic speaking skills.